From Starch to Magnetic Porous Fe2O3@C: A Promising Peroxidase‐Mimicking Heterogeneous Biocatalyst for Degradation of Organic Dye. (5th March 2018) - Su, Linjing; Xiong, Yuhao; Wu, Mei; Duan, Zhenhua; Zhang, Zhi; Xie, Wei; Zhu, Dongjian; Luo, Yanghe; He, Xingcun
Abstract : Researchers remain attracted to the development of more efficient and cost‐effective materials for the degradation of organic dyes in wastewater. Ultra‐small (sub‐5 nm) Fe2 O3 nanocrystals embedding magnetic porous carbon, referred to as Fe2 O3 @C, in which starch is used as a carbon source, is demonstrated, and is synthesized by a facile microwave‐enhanced high‐temperature ionothermal method within 4 min. The Fe2 O3 @C obtained is used as a peroxidase‐mimicking catalyst in heterogeneous Fenton‐like reactions to degrade organic dyes (i.e., methylene blue) with aid from the green oxidant, hydrogen peroxide. Because of its unique structure and high specific surface area, Fe2 O3 @C displays enhanced treatment properties in the degradation of methylene blue. Moreover, Fe2 O3 @C demonstrates stability and resistance to a broad range of pH, recyclability, and convenient separation. This promising peroxidase‐mimicking composite material may have potential applications in degradation of organic pollutants in the environmental cleaning field. Abstract : Ultrasmall (sub‐5 nm) Fe2 O3 nanocrystals embedding magnetic porous carbon (Fe2 O3 @C) are demonstrated, in which starch is used as a carbon source and is synthesized by a facile microwave‐enhanced high‐temperature ionothermal method within 4 min. The Fe2 O3 @C obtained is used as peroxidase‐mimicking catalyst in heterogeneous Fenton‐like reactions to degrade organic dyes with aid from hydrogen peroxide.